2009
DOI: 10.3346/jkms.2009.24.s1.s195
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-induced TGF-β1Expression is Regulated by Mitogen-Activated Protein Kinases and Activator Protein-1 in Mesangial Cells

Abstract: Aldosterone has been shown to stimulate renal TGF-β1 expression. However, the mechanisms for aldosterone-induced TGF-β1 expression have not been clearly determined in mesangial cells. We examined the role of extracellular-signal regulated kinase 1 and 2 (ERK1/2), c-Jun N-terminal kinase (JNK) and activator protein-1 (AP-1) in the aldosterone-induced TGF-β1 expression in rat mesangial cells. TGF-β1 protein in the conditioned medium released from rat mesangial cells was measured by sandwich ELISA, TGF-β1 mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
2
29
0
3
Order By: Relevance
“…38,39 Irbesartan and spironolactone seem to decrease the extent of peritoneal injury caused by bacterial peritonitis. 40 Aldosterone stimulates the MAPK pathway and cell-cycle progression in mesangial cells mainly via MR. 41 Another study demonstrated that aldosterone rapidly induced phosphorylation of JNK and spironolactone abolished aldosterone-induced phosphorylation of JNK, 42 which is in agreement with our findings. Spironolactone was shown to downregulate ED1, MCP-1, p-c-Jun, TGF-b1 and FN in the visceral peritoneum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…38,39 Irbesartan and spironolactone seem to decrease the extent of peritoneal injury caused by bacterial peritonitis. 40 Aldosterone stimulates the MAPK pathway and cell-cycle progression in mesangial cells mainly via MR. 41 Another study demonstrated that aldosterone rapidly induced phosphorylation of JNK and spironolactone abolished aldosterone-induced phosphorylation of JNK, 42 which is in agreement with our findings. Spironolactone was shown to downregulate ED1, MCP-1, p-c-Jun, TGF-b1 and FN in the visceral peritoneum.…”
Section: Discussionsupporting
confidence: 90%
“…Aldosterone-induced TGF-b1 expression in mesangial cells is regulated by the ERK1/2, JNK and AP-1 intracellular signaling pathways. 15 In this study, we investigated the hypothesis that aldosterone could promote peritoneal inflammation and fibrosis by stimulating the secretion of macrophages in the peritoneum, activating the JNK pathway, and further upregulating the expression of TGF-b1.…”
mentioning
confidence: 99%
“…9 Aldosterone promotes renal fibrosis by stimulating collagen synthesis via ERK1/2 phosphorylation and TGF-␤ induction. 34 miR-192 could thus participate in the multiple roles of aldosterone in health and diseases. The mechanisms by which aldosterone regulates miR-192 expression remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathologic hallmark is arteriolar vasoconstriction, which leads to glomerular ischemia (76 ). Both angiotensin II and aldosterone may independently aggravate these pathologic effects because of their stimulating effects on TGF-␤ production (75,77,78 ). Tacrolimus has a similar nephrotoxic profile, although it is seemingly somewhat less severe (79 ).…”
Section: Kidneymentioning
confidence: 99%